Legal Protection of Entrepreneurial Activity in the Republic of Uzbekistan and its Role in the Formation of Civil Society (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the legal foundations of entrepreneurship in the Republic of Uzbekistan, the mechanisms for its legal protection, and the role of entrepreneurial activity in the formation of civil society. The reforms being implemented in the country demonstrate the expansion of freedoms for business entities and the strengthening of state support in protecting their rights and interests. The paper also highlights issues such as support systems for small businesses, the development of a healthy competitive environment, and the social responsibility of entrepreneurs. Based on the results of the study, scientific and practical proposals for improving the legal framework are presented.